Twenty years of breast cancer epidemiology and treatment patterns in São Paulo, Brazil—observed versus expected treatment utilization in a retrospective cohortResearch in context - Haydee Verduzco-Aguirre; Fernanda Mallucelli Favorito; Fabio Ynoe de Moraes; Gustavo Marta; Camila Tagle; Carlos Henrique dos Anjos; André Mattar; Brooke E. Wilson (The Lancet Regional Health. Americas)
Summary: Background: Over half of new breast cancer cases occur in low- and middle-income countries, with disparities in survival outcomes due to late-stage diagnoses, healthcare access gaps, and biological differences. This retrospective cohort study examined trends in survival, stage distribution, and treatment utilization for breast cancer in Brazil, an upper middle-income country. Methods: Patients newly diagnosed with invasive breast cancer between 2000 and 2019 were identified from São Paulo’s Oncocenter Foundation registry. Data on demographics, diagnosis stage, diagnosis-to-treatment intervals, and treatments received were analyzed in 5-year blocks. Median overall survival was estimated using the Kaplan–Meier method. Actual treatment utilization was compared to model-based estimates of optimal utilization derived from the National Comprehensive Cancer Network Guidelines’ Enhanced and Maximal Resource Modules. Findings: We included 125,005 patients, with a median age at diagnosis of 55 years (interquartile range 46–75); 99.4% (n = 124,218) were female. The proportion with early disease remained stable over time (61.7% in 2000–2004, 62.4% 2015–2019). Median overall survival increased from 10.7 years (2000–2004) to 11.7 years (2010–2014); median survival for 2015–2019 was not reached. Median overall survival was 20.8, 15.1, 6.8, and 2.0 years for stages I–IV, respectively. Median diagnosis-to-treatment interval more than doubled over time. From 2000 to 2004 to 2015–2019, chemotherapy use decreased from 71.5% to 68.9%; radiotherapy use decreased from 64.0% to 56.5%, and surgery utilization decreased from 80.3% to 74.8%; endocrine therapy use varied between 54% and 62%. Gaps between observed and model-based estimates of treatment utilization were seen across all stages. Interpretation: Overall survival in patients with breast cancer in São Paulo has improved over time. However, significant treatment gaps and increasing diagnosis-to-treatment intervals suggest systemic barriers to optimal care delivery. Funding: No funding received.